Fischer's mastery of surgery - Fischer, Josef E. 1937-; Ellison, E. Christopher; Upchurch, Gilbert R.; Galandiuk, Susan 1957-; Gould, Jon; Klimberg, V. Suzanne (Wolters Kluwer, 2019)
Emphasizing both the science and craft of surgery, Fischer's Mastery of Surgery , Sixth Edition, embraces a scope consistent with the broad training of a general surgeon, providing extensive coverage of vascular surgery as well as of common thoracic, breast, esophageal, endocrine, colorectal, gastric, pancreatic, liver, and biliary procedures. Organized for ease of use, each procedural chapter reviews the essentials of diagnosis, anatomy, and pre-operative planning, but focuses most heavily on step-by-step depictions and descriptions of procedures. Each chapter concludes, as is traditional for this classic text, with an editorial commentary that puts the chapter material in a broad context and provides helpful critiques of the most recent literature